Prevalence of Citrus Canker Caused by Xanthomonas axonopodis pv. citri in Subtropical Zone of Himachal Pradesh - Kumar, Dinesh; Jarial, Kumud; Jarial, R. S.; Banyal, S. K.; Jandaik, Savita (International Journal of Bio-resource and Stress Management, 2020)
Citrus canker is most important disease of citrus causing extensive losses all over the world including India as well as in Himachal Pradesh. To record the prevalence of disease on different Citrus spp. a survey was conducted in different citrus growing areas of Himachal Pradesh during 2018 and data in terms of disease incidence (%) as well as disease severity (%) was recorded. During the survey the disease incidence was found to be ranging from 40 to 100% and disease severity ranged between 2.78% to 50.55% having maximum mean disease incidence (87.77%) as well as mean disease severity (29.07%) in district Kangra and minimum mean disease incidence (69.74%) as well as severity (11.21%) in Hamirpur district of Himachal Pradesh. The areas in which disease severity was found to be more than 15.00 %, diseased samples from those areas were collected and studied in vitro. Total nine isolates were collected and these different isolates produced yellow, pale and light yellow circular colonies with colony diameter ranging between 1.45 mm to 3.15 mm and tested positive both for protein digestion as well as esculin hydrolysis and exhibited negative reaction towards Gram’s staining. During pathogenicity test of all isolates on K. lime host as detached leaf assay, the symptoms appeared in 3.00 to 5.00 days while, 14.00 to 16.00 days time was recorded for complete symptom development under in vitro conditions.